Physical Activity Measured by Implanted Devices Predicts Atrial Arrhythmias and Patient Outcome: Results of IMPLANTED (Italian Multicentre Observational Registry on Patients With Implantable Devices Remotely Monitored). Issue 5 (24th February 2018) - Palmisano, Pietro; Guerra, Federico; Ammendola, Ernesto; Ziacchi, Matteo; Luigi Pisanò, Ennio Carmine; Dell'Era, Gabriele; Aspromonte, Vittorio; Zaccaria, Maria; Di Ubaldo, Francesco; Capucci, Alessandro; Nigro, Gerardo; Occhetta, Eraldo; et al.
Abstract : Background: To determine whether daily physical activity (PA), as measured by implanted devices (through accelerometer sensor), was related to the risk of developing atrial arrhythmias during long‐term follow‐up in a population of heart failure (HF) patients with an implantable cardioverter defibrillator (ICD). Methods and Results: The study population was divided into 2 equally sized groups (PA cutoff point: 3.5 h/d) according to their mean daily PA recorded by the device during the 30‐ to 60‐day period post‐ICD implantation. Propensity score matching was used to compare 2 equally sized cohorts with similar characteristics between lower and higher activity patients. The primary end point was time free from the first atrial high‐rate episode (AHRE) of duration ≥6 minutes. Secondary end points were: first AHRE ≥6 hours, first AHRE ≥48 hours, and a combined end point of death or HF hospitalization. Data from 770 patients (65±15 years; 66% men; left ventricular ejection fraction 35±12%) remotely monitored for a median of 25 months were analyzed. A PA ≥3.5 h/d was associated with a 38% relative reduction in the risk of AHRE ≥6 minutes (72‐month cumulative survival: 75.0% versus 68.1%; log rank P =0.025), and with a reduction in the risk of AHRE ≥6 hours, AHRE ≥48 hours, and the combined end point of death or HF hospitalization (all P <0.05). Conclusions: In HF patients with ICD, a low level of daily PA was associated with a higher risk of atrial arrhythmias, regardless of the patients' baseline characteristics. In addition, a lower daily PA predicted death or HF hospitalization.